Tecnologías de información y comunicación en el ámbito educativo (Revista Electrónica REDINE, 2018)
The technology education, school activity involves both the technical and cultural in a relationship desirable theoretical and practical, is a promising contribution to the demystification and democratization of science and technology. The integration of information technology and communication (ICT) in society and especially in the field of education has been gaining increasing importance and has evolved over the last few years, while the use of these in the classroom will be a chance to establish itself as a necessity and as a basic tool for the teacher and the student. The emergence of ICT has been a profound change in a society that has gone in vain be called information society.
Keywords: TICs